Clinical and subclinical effects of power brushing following experimental induction of biofilm overgrowth in subjects representing a spectrum of periodontal disease. (6th October 2013) - Aspiras, Marcelo B.; Barros, Silvana P.; Moss, Kevin L.; Barrow, David A.; Phillips, Sherrill T.; Mendoza, Luis; de Jager, Marko; Ward, Marilyn; Offenbacher, Steven
Abstract: Aim: Investigate short‐term effects of power brushing following experimental induction of biofilm overgrowth in periodontal disease states. Materials and Methods: Overall, 175 subjects representing each of five biofilm–gingival interface (BGI) periodontal groups were enrolled in a single‐blind, randomized study. After stent‐induced biofilm overgrowth for 21 days subjects received either a manual or a power toothbrush to use during a 4 weeks resolution phase. At baseline and during induction and resolution, standard clinical parameters were measured. Subclinical parameters included multikine analysis of 13 salivary biomarkers and 16s Human Oral Microbe Identification Microarray (HOMIM) probe analysis of subgingival plaque samples. Results: All groups exhibited significantly greater reductions in bleeding on probing (BOP) ( p  = 0.002), gingival index (GI) ( p  = 0.0007), pocket depth (PD) ( p  = 0.04) and plaque index ( p  = 0.001) with power brushing compared to manual. When BGI groups were combined to form a shallow PD (PD ≤ 3 mm) and a deep PD group (PD > 4 mm) power brushing reduced BOP and GI in subjects with both pocket depths. Power brushing significantly reduced IL‐1β levels at resolution while changes in bacterial levels showed non‐significant trends between both brushing modalities. Conclusions: Short‐term changes in select clinical parameters and subclinical salivary biomarkers may be useful in assessing efficacy of power brushing interventions in a spectrum of periodontal disease states.